Blood flow simulations in patient-specific geometries of the carotid artery: A systematic review. (9th October 2020) - Lopes, D.; Puga, H.; Teixeira, J.; Lima, R.
Abstract: Computational Fluid Dynamics (CFD) and Fluid-Structure Interaction (FSI) are currently widely applied in the study of blood flow parameters and their alterations under pathological conditions, which are important indicators for diagnosis of atherosclerosis. In this manuscript, a systematic review of the published literature was conducted, according to the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses, on the simulation studies of blood flow in patient-specific geometries of the carotid artery bifurcation. Scopus, PubMed and ScienceDirect databases were used in the literature search, which was completed on the 3rd of August 2020. Forty-nine articles were included after the selection process and were organized in two distinct categories: the CFD studies (36/49 articles), which comprise only the fluid analysis and the FSI studies (13/49 articles), which includes both fluid and Fluid-Structure domain in the analysis. The data of the research works was structured in different categories (Geometry, Viscosity models, Type of Flow, Boundary Conditions, Flow Parameters, Type of Solver and Validation). The aim of this systematic review is to demonstrate the methodology in the modelling, simulation and analysis of carotid blood flow and also identify potential gaps and challenges in this research field.